Podoplanin is dispensable for mineralized tissue formation and maintenance in the Swiss outbred mouse background. Issue 10 (6th September 2021) - Toda Nakamura, Masako; Zhang, Honghao; Guo, Dayong; Ueharu, Hiroki; Pan, Haichun; Scott, Greg; Harris, Marie; Ray, Manas; Feng, Jiang Q.; Harris, Stephen E.; Bonewald, Lynda F.; Mishina, Yuji
Summary: Podoplanin, PDPN, is a mucin‐type transmembrane glycoprotein widely expressed in many tissues, including lung, kidney, lymph nodes, and mineralized tissues. Its function is critical for lymphatic formation, differentiation of type I alveolar epithelial lung cells, and for bone response to biomechanical loading. It has previously been shown that Pdpn null mice die at birth due to respiratory failure emphasizing the importance of Pdpn in alveolar lung development. During the course of generation of Pdpn mutant mice, we found that most Pdpn null mice in the 129S6 and C57BL6/J mixed genetic background die at the perinatal stage, similar to previously published studies with Pdpn null mice, while all Pdpn null mice bred with Swiss outbred mice survived. Surviving mutant mice in the 129S6 and C57BL6/J mixed genetic background showed alterations in the osteocyte lacunocanalicular network, especially reduced osteocyte canaliculi in the tibial cortex with increased tibial trabecular bone. However, adult Pdpn null mice in the Swiss outbred background showed no overt differences in their osteocyte lacunocnalicular network, bone density, and no overt differences when challenged with exercise. Together, these data suggest that genetic variations present in the Swiss outbred mice compensate for the loss of function of PDPN in lung, kidney, and bone.